PEMANFAATAN LIMBAH KULIT UDANG WINDU (Penaeus monodon) SEBAGAI EDIBLE COATING DAN PENGARUHNYA TERHADAP KADAR ION LOGAM Pb(II) PADA BUAH STROBERI (Fragaria x ananassa) - Marzuki, Qosim (Chem Info Journal, 2013)
A study on the utilization of leather wastes tiger shrimp (Penaeus monodon) as an edible coating and effect of Pb (II) in strawberries (Fragaria x ananassa). This research aims to synthesize chitosan from chitin of the shrimp shell waste, to determine the optimum concentration of chitosan as edible coating and determine the effect of chitosan to adsorption Pb (II) on the surface of strawberries. Experiment were carried out in several stages of research starting with the isolation of chitin by demineralitation and deproteination and than transforming it into the chitosan by deacetylation. The result is then analyced by of FTIR. Further manufacture of edible coating, the coating of fruit, and analysis of fruit quality after coating, including testing of acidity (pH) strawberries, Vitamin C, and test Pb metal adsorption on the surface of the fruit, and organoleptic test was done visual observation of physical appearance of strawberries. The results obtained chitosan can be synthesized from shrimp shell waste with 70.03% degree of deacetylation. Chitosan 2% as the coating was able to maintain the qulity of strawberries fruit longer than without coating until the fifth day. Chitosan as coating agent was also able to reduce the presence of metal ions Pb2+ on the strawberries surface